Editorial Note for the Special Issue on Multi-Objective and Goal Programming: Theory and Applications - Aouni, Belaid; Abdelaziz, Fouad Ben (INFOR. Information systems and operational research, 2014)
This special issue of INFOR on "Multi-Objective Programming: Theory and Applications" is devoted to some papers presented at the International Conference on Modeling, Simulation and Applied Optimization held at Hammamat (Tunisia) on April 28-30, 2013. This scientific event was organized by the Tunisian Decision Aid Society that promotes the development and the use of quantitative tools for improving decision-making processes within public and private organizations. These tools include decision-making models for problems under uncertainty, multi-criteria decision aid approaches, risk analysis and assessment, descriptive and prescriptive studies for strategic decision, and group decision-making. The aim of this conference is to provide an international forum for presentations and discussion of research in all areas of science and engineering involving the modeling and simulation of processes and systems. The selected papers for this special issue deal with some new theoretical developments and applications of Multi-Objective Programming and Goal Programming that have been presented in this conference. Our thanks go to the authors and the peer reviewers for their valuable input and enthusiasm and the most agreeable and efficient cooperation.